2021
DOI: 10.1101/2021.02.04.21251131
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using Machine Learning to Predict Mortality for COVID-19 Patients on Day Zero in the ICU

Abstract: Rationale Given the expanding number of COVID-19 cases and the potential for upcoming waves of infection, there is an urgent need for early prediction of the severity of the disease in intensive care unit (ICU) patients to optimize treatment strategies. Objectives Early prediction of mortality using machine learning based on typical laboratory results and clinical data registered on the day of ICU admission. Methods We studied retrospectively 263 COVID-19 ICU patients. To find parameters with the highest pred… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The pooled mean difference of the MPV values was significantly higher in the severe group (SMD = 0.34 [95% CI: 0.14, 0.53], p = 0.0006, n = 1,337); however, there was substantial heterogeneity by the random effect model ( I 2 = 55%) (Supplementary material 5: Figure 1). Sensitivity analysis based on blood tests taken at hospital admission for four studies [19, 24, 25, 38] showed similar results (SMD = 0.40 [95% CI: 0.19, 0.61], p = 0.0002, n = 849) and heterogeneity ( I 2 = 50%). Similar results and heterogeneity were also shown for sensitivity analysis based on the clinical outcome by excluding Barrett et al [25] (SMD = 0.31 [0.10, 0.52], p = 0.004, n = 1237, I 2 = 59%).…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…The pooled mean difference of the MPV values was significantly higher in the severe group (SMD = 0.34 [95% CI: 0.14, 0.53], p = 0.0006, n = 1,337); however, there was substantial heterogeneity by the random effect model ( I 2 = 55%) (Supplementary material 5: Figure 1). Sensitivity analysis based on blood tests taken at hospital admission for four studies [19, 24, 25, 38] showed similar results (SMD = 0.40 [95% CI: 0.19, 0.61], p = 0.0002, n = 849) and heterogeneity ( I 2 = 50%). Similar results and heterogeneity were also shown for sensitivity analysis based on the clinical outcome by excluding Barrett et al [25] (SMD = 0.31 [0.10, 0.52], p = 0.004, n = 1237, I 2 = 59%).…”
Section: Resultsmentioning
confidence: 84%
“…Wu et al [20] was an international multi-centre study, but we extracted data for patients recruited from one centre. Five studies were identified from preprint databases [20-24]. The disease outcomes for 16 studies were severity of COVID-19, and seven studies assessed mortality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, complications are common among elderly patients and those with pre-existing conditions. The intensive care unit (ICU) admission rate is substantially higher for these groups ( Abate et al, 2020 ; Jamshidi et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%